Imaging of the lamina cribrosa and its role in glaucoma: a review. (10th January 2018) - Tan, Nicholas YQ; Koh, Victor; Girard, Michaël JA; Cheng, Ching‐Yu
Abstract: The lamina cribrosa of the optic nerve head serves two contrasting roles; it must be porous to allow retinal ganglion cell axons to pass through, and yet at the same time, it must also provide adequate structural support to withstand the stresses and strains across it. Improvements in imaging such as optical coherence tomography image capture and image processing have allowed detailed in vivo studies of lamina cribrosa macro‐ and micro‐architectural characteristics. This has aided our understanding of the optic nerve head as a complex biomechanical structure. In this review, we first aim to frame the biomechanical considerations of lamina cribrosa in a clinical context; in doing so, we also explore the concept of the translaminar pressure difference. Second, we aim to highlight the technological advances in imaging the lamina cribrosa and its accompanying clinical implications, and future directions in this quickly progressing field.